Aplikasi Pendaftaran dan Pengelolaan Magang pada Bank BRI Cabang Banjarmasin Samudera Berbasis Web - Puad Sayed (Journal Information Technology Trends (JITRENDS), 2025)
Bank BRI Banjarmasin Samudera Branch receives internship applications from students every year. The registration process, document selection, testing process, and internship participant management are still conducted manually, causing inefficiencies and increasing the risk of data loss or damage. This study aims to develop a web-based internship registration and management application to support registration, selection, testing, attendance, and participant assessment processes. The system was designed using Data Flow Diagrams (DFD) and implemented using PHP, MySQL, and Apache. System testing was conducted using the Black Box Testing method to ensure that all functions operated according to user requirements. The results show that the application is capable of managing internship documents, online tests, internship participant data, attendance records, assessments, and user data in an integrated manner. Based on the testing results, all main functions of the system operate properly according to user requirements. Therefore, the developed application improves the effectiveness and efficiency of internship management activities at Bank BRI Banjarmasin Samudera Branch.